Detailed analysis of metastatic colorectal cancer patients who developed cardiotoxicity on another fluoropyrimidine and switched to S-1 treatment (subgroup analysis of the CardioSwitch-study) - Kinos, Sampsa (Taylor & Francis, 2026)
Background and purpose: The CardioSwitch-study demonstrated that patients with solid tumors who develop cardiotoxicity on capecitabine or 5-fluorouracil (5-FU) treatment can be safely switched to S-1, an alternative fluoropyrimidine (FP). In light of the European Medicines Agency approval of S-1 in metastatic colorectal cancer (mCRC), this analysis provides more detailed safety and efficacy information, and data regarding metastasectomy and/or local ablative therapy (LAT), on the mCRC patients from the original study.
Materials and methods: This retrospective cohort study was conducted at 12 European centers. The primary endpoint was recurrence of cardiotoxicity after switch. For this analysis, safety data are reported for 78 mCRC patients from the CardioSwitch cohort (N = 200). Detailed efficacy and outcomes data were available for 66 mCRC patients.
Results: Data for the safety of S-1 in mCRC patients were similar to the original CardioSwitch cohort and that expected for FP-based treatment, with no new concerns. Recurrent cardiotoxicity (all grade 1) with S-1-based treatment occurred in 4/78 (5%) mCRC patients; all were able to complete FP treatment. Median progression-free survival from initiation of S-1-based treatment was 9.0 months and median overall survival 26.7 months. Metastasectomy and/or LAT was performed in 33/66 (50%) patients, and S-1 was successfully used in recommended neoadjuvant/conversion or adjuvant-like combination regimens and schedules as for standard FPs.
Interpretation: S-1 is a safe and effective FP alternative when mCRC patients are forced to discontinue 5-FU or capecitabine due to cardiotoxicity and can be safely used in the standard recommended regimens, settings, and schedules.